Design and development of new zinc porphyrin molecules as high performing photoacoustic contrast agents - Yasin, Amina (2018)
This doctoral research aims to design and develop new porphyrin molecules as contrast agents in photoacoustic (PA) imaging (PAI) such as PA tomography and PA microscopy. For successful implementation of PAI techniques, contrast agents exhibiting large PA coefficients are one of the essential requirements. Many materials, either endogenous biomolecules such as haemoglobin, deoxyhaemoglobin, melanin or exogenous materials such as organic molecules, clusters or nanocrystals are shown to exhibit PA effects. However, they are either limited by poor PA coefficients, poor penetration depths or toxicity. Development of new PA molecules is limited because the factors influencing the PA effect have rarely been systematically studied, resulting in a lack of guidance for the design of molecular PA contrast agents. In this thesis, it is hypothesized that large PA effects could be achieved if vibrations of the molecular or functional groups lying above the atoms composing the lowest unoccupied molecular orbitals could be manipulated in such a way that the oscillator strength of those vibrations increase upon suitable chemical modification, then a large portion of the excited photons can be thermalized via phonon emission. By using Zn(II)porphyrin as a model system, a large number of molecules were modelled using state of the art density functional theory (DFT) based on the above assumption and their ground and excited state properties were studied systematically by using the Becke’s three-parameter hybrid method with the Lee, Yang, and Parr gradient corrected correlation functional (B3LYP) with the effective core potential employing basis sets of LANL2DZ and 6-31G(d) using the Gaussian 09W program package. It was observed that less resonating functional groups in a phenyl group attached to the porphyrin core amplify the oscillation strengths of the alkoxy groups – a systematic variation in the absorption coefficients of the C-H vibrational modes was observed with relative change in the resonance of the molecular groups anchored. Motivated from this result, representative four Zn(II)porphyrin molecules (RJ-Cn-MYm, where n = 12 or 8 and m = 1 – 4) were synthesized in good yields by acid-catalyzed oxidation, Knoevenagel condensation, MacDonald (2+2) condensation, bromination, metalation, deprotection, and Sonogashira coupling reactions. Structure of the molecules were studied by NMR, Mass Spectrometry, and FTIR spectroscopy; optical properties were studied by UV-Vis absorption spectroscopy, photoluminescence spectroscopy, and time-correlated single photon counting; and PA properties were studied by photoacoustic spectroscopy. The absorption coefficient decreased in the order of RJ-C12-MY1> RJ-C12-MY2> RJ-C12-MY3 > RJ-C8-MY4; and therefore, a similar variation in the PA signals was predicted. Theoretical predictions were validated by PA coefficients measurements and PA tomography. The PA coefficients and tomographic intensities decreased in the order RJ-C12-MY1> RJ-C12-MY2> RJ-C12-MY3 > RJ-C8-MY4, as predicted by DFT. The detailed molecular characterizations in determining the nature of optoelectronic properties i.e.; ground state molar extinction coefficients, excited state molar extinction coefficients, fluorescence quantum yields and excited state lifetimes of newly synthesized Zn(II)porphyrin molecules were examined in order to show the positive correlation between vibrational energy levels, molar extinction coefficients, phonon emitting states and PA effect. Large PA coefficients were observed for the RJ-C12-MY1, providing an up to ⁓7-fold PA enhancement over that of ZnTPP used as a reference, which is superior to that of the existing small molecules. Besides offering a superior molecule for PA tomography, the present thesis and criterion adopted here would enable to design simpler molecules with superior photoacoustic and other nonlinear optical properties.